Evaluation of Treatment Outcomes and Quality of Life of MDR-TB Patients at Raden Mattaher Hospital Jambi - Nopridayanti, Nopridayanti; Ramatillah, Diana Laila; Miranda, Melly; Herlambang, Herlambang (International Journal Labs, 2025)
Multidrug-resistant tuberculosis (MDR-TB) poses a significant challenge to TB control efforts in Indonesia, primarily due to its complex, long-term treatment and significant drug side effects. To date, there is no comprehensive evaluation data on treatment outcomes and quality of life of MDR-TB patients at Raden Mattaher Regional Hospital, Jambi Province. This study aims to evaluate treatment outcomes and health-related quality of life in MDR-TB patients, as well as to identify predictors influencing therapy outcomes. This study used an observational design with a retrospective approach, analyzing medical records of MDR-TB patients from 2020 to 2024. The WHOQOL-BREF instrument was used to measure quality of life. Bivariate and multivariate analyses were conducted to evaluate the association between patient characteristics and treatment outcomes. Most MDR-TB patients demonstrated successful treatment outcomes, but quality of life in the physical (score 45.2) and environmental (score 48.5) domains was relatively low. Side effects of second-line drugs, such as nausea, neuropathy, and hearing loss, contributed to the low physical domain scores. Multivariate test results showed that comorbid diabetes mellitus (DM) was a significant predictor of treatment outcomes (p = 0.007). The quality of life of MDR-TB patients at Raden Mattaher Regional Hospital in Jambi remains low, primarily influenced by side effects of therapy and the presence of comorbidities such as DM, which have been shown to impact treatment outcomes. More integrated interventions between TB management and comorbidities are urgently needed. Patients should be educated about side effects and the importance of treatment adherence. Hospitals are advised to improve side effect monitoring and integrate comorbidity management.